Pengembangan Model Pembelajaran Bola Kecil Untuk Siswa Sekolah Dasar - Kartyas Argya Pradana; Mu'arifin Mu'arifin; Sapto Adi (Universitas Negeri Malang, 2021)
This study aims to develop and test a product in the form of a small ball learning video for elementary school students in the city of Malang. The results of this study: (1) validation of media experts by 100% (very valid), (2) validation of learning experts by 83.3% (very valid), and (3) material experts by 75% (quite valid). Small group trials that assessed convenience and attractiveness got percentages of 86.8% and 93.5%, respectively (very valid), and (4) large group trials conducted at SDN Blimbing 3 Malang and SDN Karangbesuki 3 Malang got percentages of 87.2% and 89.8%, respectively (very valid). Based on the research that has been finished, it can be concluded that this product is suitable for use in PJOK learning in the COVID-19 phase.